186k views
0 votes
Plzzzzzzzzzzzzz help

Plzzzzzzzzzzzzz help-example-1
User Mpx
by
4.7k points

2 Answers

2 votes

Answer: 4m²-28m+49

Explanation:

(2m-7)² can be written as (2m-7)(2m-7).

You would have to multiply it out like this:

2m times 2m=4m² (2x2=4 and mxm=m²)

2m times -7=-14m (2x-7=-14 then put a m on it)

-7 times 2m=-14m

-7 times -7=49

The equation would then look like this:

4m²-14m-14m+49

Then you would have to collect like terms. Like terms are terms with the same variables and powers. It will then look like this:

4m²-28m+49

Hope this helps :)

User Grifos
by
5.1k points
5 votes
(2m-7)(2m-7)
4m^2 - 14m - 14m + 49
4m^2 - 28m + 49
User RVP
by
5.1k points